2003
DOI: 10.1002/ajmg.b.20115
|View full text |Cite
|
Sign up to set email alerts
|

Is the WKL1 gene associated with schizophrenia?

Abstract: A missense mutation Leu309Met in the WKL1 (MLC1, KIAA0027) gene, mapped to 22q13.3, was reported to co-segregate with periodic catatonic schizophrenia (SCZ) in a single large German pedigree with seven affected individuals (Meyer et al. [2001: Mol Psychiatry 6:302-306]). This report raised the following questions that were dealt with in the present study: does the Leu309Met mutation have a role in SCZ, or only in catatonic SCZ? Does the mutation Leu309Met in the WKL1 gene, encoding a putative membrane protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…34 However, both the same group and others have more recently rejected this hypothesis based on more extensive analyses of a number of catatonic families. [35][36][37] Interestingly, a recent study of a Southern Indian population reported evidence of association between MLC1 and both SZ and BPD. 38 According to the regional LD pattern discussed above it does not seem likely that the Indian MLC1 signal and the present BRD1 association represent the same susceptibility locus, unless the population of Southern India has a different and more extended LD pattern.…”
Section: Discussionmentioning
confidence: 99%
“…34 However, both the same group and others have more recently rejected this hypothesis based on more extensive analyses of a number of catatonic families. [35][36][37] Interestingly, a recent study of a Southern Indian population reported evidence of association between MLC1 and both SZ and BPD. 38 According to the regional LD pattern discussed above it does not seem likely that the Indian MLC1 signal and the present BRD1 association represent the same susceptibility locus, unless the population of Southern India has a different and more extended LD pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The sixth polymorphism, c.925C4A, has been debated in several works [Devaney et al, 2002;Kaganovich et al, 2004;Leegwater et al, 2002a,b;McQuillin et al, 2002;Meyer et al, 2001;Rubie et al, 2003;Teijido et al, 2004], which describe the possible association of a leucine to methionine change at position 309 with schizophrenia. A recent work reported on the association of schizophrenia and bipolar disorder with MLC1 mutations [Verma et al, 2005].…”
Section: Polymorphismsmentioning
confidence: 99%
“…Based on the myelin vacuolation present in MLC patients and the low homology of MLC1 to ion channels, it has been suggested that MLC1 could have a role in ion transport processes linked to water movements. Unfortunately, functional evidence is lacking, because no ion channel activity has been detected after expression of MLC1 in heterologous systems (Kaganovich et al, 2004; Teijido et al, 2004). …”
Section: Introductionmentioning
confidence: 99%